MEGen: A Physiologically Based Pharmacokinetic Model Generator - Loizou, George D.; Hogg, Alex (Frontiers in Pharmacology, 2011)
Physiologically based pharmacokinetic models are being used in an increasing number of different areas. These not only include the human safety assessment of pharmaceuticals, pesticides, biocides and environmental chemicals but also for food animal, wild mammal and avian risk assessment. The value of PBPK models is that they are tools for estimating tissue dosimetry by integrating in vitro and in vivo mechanistic, pharmacokinetic and toxicological information through their explicit mathematical description of important anatomical, physiological and biochemical determinants of chemical uptake, disposition and elimination. However, PBPK models are perceived as complex, data hungry, resource intensive and time consuming. In addition, model validation and verification are hindered by the relative complexity of the equations. To begin to address these issues a freely available web application for the rapid construction and documentation of bespoke PBPK models is under development. Here we present an overview of the current capabilities of MEGen, a model equation generator and parameter database and discuss future developments.